Pengaruh Motivasi dan Mental Berwirausaha Terhadap Jiwa Berwirausaha Mahasiswa STIE Canda Bhirawa Kediri - Anita Kumala Sari; Sinollah Sinollah (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
The influence of entrepreneurship education so far has been considered as one of the important factors for growing and developing entrepreneurial passion, spirit and behavior among the younger generation. Related to the influence of entrepreneurship education, it is necessary to have an understanding of how to develop and encourage the birth of potential young entrepreneurs while they are still in school. Several previous studies stated that students' entrepreneurial desires are a source for the birth of future entrepreneurs. This study aims to obtain empirical evidence regarding the influence of entrepreneurial motivation and mentality on the entrepreneurial spirit of STIE Canda Bhirawa Kediri students. To obtain the required sample, a census was carried out by way of direct interviews with students. After conducting a census of 30 STIE Canda Bhirawa Kediri students who were entrepreneurs. Because the population < 100 people. The data in this study were obtained by collecting primary data in the form of a questionnaire. then analyzed using quantitative research methods and qualitative research methods and tested with the z test and t test. From the test results it was concluded that the suitability of the resulting regression analysis model is suitable for knowing the influence of motivation and mental entrepreneurship on the entrepreneurial spirit of STIE Canda Bhirawa students. For this reason, it is necessary that the motives and mentality of entrepreneurship among students must be maintained and maybe even elaborated by managers (universities in particular) into the curriculum in providing students with provisions to enter the world of work after graduation. The weakness of this study is only on a sample of students at one tertiary institution. It is recommended for further research to use a larger sample with several tertiary institutions in order to make better generalizations, besides that it can make a distinction regarding the motivation and mentality of entrepreneurship between students and female students, where in this study it turned out that 67% of entrepreneurs are female students.